Peroxy‐Benzoic Acid Mediated Domino C[sp2] Hydroxylation /Annulation of Enaminones for the Synthesis of 3‐Hydroxy Chromones. Issue 23 (22nd June 2020) - Gudipati, Ramakrishna; Kandula, Venu; Raghavulu, K.; Basavaiah, K.; Yennam, Satyanarayana; Behera, Manoranjan
Abstract: An efficient, facile, and clean synthesis of various 3‐hydroxy‐chromones (3‐hydroxy‐4H‐chromene‐4‐ones) via enamino ketone followed by cyclization using m‐chloroperbenzoic acid (MCPBA) has been described. The significant features of this method include simple method, high purity and excellent regio‐selectivity of the products. This is the first report for the two step one pot synthesis of 3‐hydroxyl chromone using MCPBA. Abstract : A simple and novel method for preparation of 3‐hydroxy‐chromone using m‐chloroperbenzoic acid (MCPBA) has been described starting from 2‐hydroxy‐acetophenone via enaminone. The method avoids the isolation and purifcation of poetential hazardous epoxide intermediates. The reaction conditions are simple and sufficiently mild to tolerate the various functional groups that can serve as levers for further extension of chromone products.